THE RECONSTRUCTION OF THE IMAGE OF JAVANESE AS AN OLD LANGUAGE THROUGH AN ENGLISH TRANSLATION OF JAVANESE CULTURAL TERMS IN INDONESIAN NOVEL ‘GADIS KRETEK’ - Hardiyanti, Diana; Nugraheni, Yunita; Nababan, Mangatur; Santosa, Riyadi (Indonesian Journal of Applied Linguistics, 2021)
As on old language, Javanese has its uniqueness. The uniqueness of Javanese language is reflected through the use of speech level and the distinctive specification in addressing things and activities. Consequently, Javanese language is rich with vocabularies and it has many specific cultural terms in many aspects and activities. In Indonesian novel ‘Gadis Kretek’, many Javanese cultural terms are incorporated to depict and construct Javanese social life, characterization, and issues. Such cultural terms become a challenge for the English translator since they symbolize the oldness of Javanese language. This research unfolds the translation techniques used by translator in translating Javanese cultural terms in novel ‘Gadis Kretek’ as well as the translation quality of the English translation. The data of this study were taken based on the certain criteria of cultural terms in Javanese found in the original novel ‘Gadis Kretek’ and its English translation ‘Cigarette Girl’. The data source was in the form of documents and informants. The documents included the original novel ‘Gadis Kretek’ and its English translation ‘Cigarette Girl’. The informants were the raters who assessed the quality of translation. This study concludes based on the translation techniques used and the finding of the translation quality, the translator is not very successful in the attempt of reconstructing the image of Javanese as an old language because the translator fails as shown in many analyzed data to deliver the specifics of Javanese cultural terms, at least their concept in the translation.